The firm beyond the market - Phillips, Duygu; Jones, Shawn (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
BYLUND, Per L. The problem of production: a new theory of the firm. Londres: Routledge, 2015. 194p.